A comparative study of Chinese women 3 × 3 basketball players exercise load in Tokyo Olympic preparation cycle - Wang, Z.; Cao, G.; Xu, J.; Qiu, J.; Yang, R. (Frontiers in Physiology, 2023)
Objective: The aim of this study was to compare the variances in-game loads exhibited by Chinese women`s 3 × 3 basketball team across different stages of the preparation cycle for the Tokyo Olympic Games, and to summarize the fundamental regulations governing Chinese women`s 3 × 3 basketball training and games, in order to establish a theoretical research foundation for the team`s new preparation cycle.